2019
DOI: 10.1111/jcpp.13179
|View full text |Cite
|
Sign up to set email alerts
|

Pupil dilation during visuospatial orienting differentiates between autism spectrum disorder and attention‐deficit/hyperactivity disorder

Abstract: Background: Previous research demonstrated atypical attention in children with attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD). Regarding visual orienting, findings suggest a differential impairment: Atypical orienting to relatively unexpected targets in ASD, and atypical processing of alerting cues in ADHD. The locus coeruleus-norepinephrine (LC-NE) system plays an important role in exploiting alerting cues to increase attention and task performance. The present study's aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…Delayed orienting of attention could be reflected by a delayed latency in the study by Bast et al, which would be in agreement with the known delayed orienting in ASD in behavioural tasks (Bast et al, 2019). Boxhoorn et al (2020) suggest increased pupil dilation is a result of a persistent hyperphasic state, with enhanced attentional focus, but also reflects increased task difficulty or cognitive load, which as a result leads them to interpret increased pupil dilation in the ASD group in their study as a higher effort to control the focus of attention during reflexive orienting in ASD. Del Valle Rubido et al (2020) suggest pupil size might reflect the ability to better arrange effortful attention and interpret this as a sign of greater cognitive or inhibitory control, even though this appears to be inconsistent with their own results.…”
Section: Cognitive Functioning Mental Effort and Attentionsupporting
confidence: 84%
“…Delayed orienting of attention could be reflected by a delayed latency in the study by Bast et al, which would be in agreement with the known delayed orienting in ASD in behavioural tasks (Bast et al, 2019). Boxhoorn et al (2020) suggest increased pupil dilation is a result of a persistent hyperphasic state, with enhanced attentional focus, but also reflects increased task difficulty or cognitive load, which as a result leads them to interpret increased pupil dilation in the ASD group in their study as a higher effort to control the focus of attention during reflexive orienting in ASD. Del Valle Rubido et al (2020) suggest pupil size might reflect the ability to better arrange effortful attention and interpret this as a sign of greater cognitive or inhibitory control, even though this appears to be inconsistent with their own results.…”
Section: Cognitive Functioning Mental Effort and Attentionsupporting
confidence: 84%
“…A recent review from Bast et al (2018) suggests that LC dysfunction might be associated with attentional differences in ASD, but there has been little prior empirical evidence to support this hypothesis. Several studies have shown phasic pupillary response differences in ASD (Martineau et al, 2011;Blaser et al, 2014;Nuske et al, 2014a,b;Krach et al, 2015;Lawson et al, 2017;Aguillon-Hernandez et al, 2019;Boxhoorn et al, 2019). However, in these studies, participants with ASD exhibited differences in task performance compared with controls; thus, differences in pupil dilations may be attributable to differences in task performance.…”
Section: Discussionmentioning
confidence: 95%
“…The LC is the main location of a highly flexible, adaptable noradrenergic system projecting in many cortical and subcortical brain regions, thus explaining its highly relevant function in humans in everyday life, and essential for us humans as feeling and thinking beings. Beside its involvement in cognitive processes, a broader function recently emerged covering aspects of psychopathology, such as triggering anxiety (Morris et al, 2020), psychosis in alpha-synucleinopathies (Wolters, 2001) and demotivation in schizophrenia (Mäki-Marttunen et al, 2020), inattention to visual stimuli in the attention deficit-hyperactivity and autism-spectrum disorders (Boxhoorn et al, 2020), depressive symptoms in Alzheimer's disease (AD) (Förstl et al, 1992), suicide behavior (Roy et al, 2017) and defective emotional-memory encoding (Jacobs et al, 2020).…”
Section: Introductionmentioning
confidence: 99%